Occurrence of Cordyceps sinensis in Upper Himalaya , Dharchula Sub-division , Pithoragarh District , Uttaranchal , India - Garbyal, S. S. (Indian Forester, 2001)
Cordyceps sinensis a insect pathogen has now been reported for the first time from Uttaranchal Himalaya , India. It has very high medicinal properties. Therefore during the year 2001 it was sold at the rate of Rs. 80 ,000 per kilogram.